Проблема ціннісних орієнтацій в системі гуманітарних наук (філософський і психологічний аспект) - Мурзіна, Олена Анатоліївна (ЗНУ, 2011)
There is no doubt that the presence of the persistent ideological beliefs is the necessary precondition of successful work of professionals of the humanitarian profile. The formation of such beliefs is possible only under the condition of creation of system of values in the consciousness of personality. At the same time it is impossible without consideration of philosophical and psychological aspects in its preparation.
Keywords: цінності; ціннісні орієнтації; мотив; ставлення; інтерес; потреби